Axial Diameter is Superior to Volumetric Measurement in Predicting Ureteral Stone Passage. Issue 5 (23rd September 2021) - Patel, Parth M.; Kandabarow, Alexander M.; Chen, Victor S.; Slovacek, Hannah; Mian, Abrar; Hart, Spencer; Farooq, Ahmer; Turk, Thomas M. T.; Baldea, Kristin G.
Abstract: Introduction: We sought to investigate the clinical utility of volumetric measurements in predicting passage of symptomatic ureteral calculi. Methods: We performed a retrospective review of patients seen in the emergency department for computerized tomography–confirmed symptomatic ureteral calculi with a subsequent discharge for trial of passage. Patient demographics and results of the passage trial were recorded. Stone parameters including location, 2-dimensional linear measurements and 3-dimensional volume measurements were calculated. Univariate and multivariate analyses were performed to evaluate the association between the aforementioned stone parameters and stone passage. Results: A total of 70 patients were analyzed, of whom 37 (53%) passed their stones. On univariate analysis, patients who passed their stones had shorter axial diameters (mean±SD 3.3±1.3 mm vs 5.1±1.7 mm, p <0.01) and smaller volumes (0.03±0.02 cm 3 vs 0.10±0.08 cm 3, p <0.01). Stones that passed had traversed 79% of the ureter on presentation, compared to 41% for the stones that did not pass (p <0.01). Multivariate analysis demonstrated that shorter axial diameter was independently associated with stone passage (OR 0.46 [CI 0.29–0.71], p <0.01). Inclusion of stone volume measurements into the logistic regression model, however, provided no additional benefit for predicting stone passage rates (p=0.28). Conclusions: Although a stone's volume is expectedly correlated with passage, it does not seem to provide additional benefit when the stone's axial diameter and location within the ureter are known. Based on our findings, additional investment of time and resources into 3-dimensional modalities may not be warranted in this setting.